Reforming the EU Fiscal Framework : Strengthening the Fiscal Rules and Institutions - Arnold, Nathaniel (Departmental Papers; Departmental Paper, 2022)
The EU's fiscal framework needs reform. While existing fiscal rules have had some impact in constraining deficits, they did not prevent deficits and debt ratios that have threatened the stability of the monetary union in the past and that continue to create vulnerabilities today. The framework also has a poor track record at managing trade-offs between containing fiscal risks and stabilizing output. Finally, the framework does not provide sufficient tools for EU-wide stabilization. This was most visible during the decade following the euro area sovereign debt crisis, when structurally low real interest rates stretched the policy tools of the European Central Bank (ECB), leading to a persistent undershooting of its inflation target. This paper proposes a new framework based on risk-based EU-level fiscal rules, strengthened national institutions, and a central fiscal capacity. First, risk-based EU-level fiscal rules would link the speed and ambition of fiscal consolidation to the level and horizon of fiscal risks, as identified by debt sustainability analysis (DSA) using a common methodology developed by a new and independent European Fiscal Council (EFC). The 3 percent deficit and 60 percent debt reference values would remain. Second, all member countries would be required to enact medium-term fiscal frameworks consistent with the EU-level rules-that is, to ensure convergence over the medium-term to an overall fiscal balance anchor by setting expenditure ceilings. Independent national fiscal councils (NFCs) would have a much stronger role to strengthen checks and balances at the national level (including undertaking or endorsing macroeconomic projections and performing DSAs to assess fiscal risks). The European Commission (EC) would continue to play its key surveillance role as articulated in the Maastricht Treaty and the EFC would be the center of a peer network of fiscal councils. Third, building on the recent experience with the NextGenerationEU (NGEU), an EU fiscal capacity (FCEU) would improve euro area macroeconomic stabilization and allow the provision of common EU public goods-a task that has become more urgent given the green transition and common security concerns. Central to the proposal is a mutually reinforcing relationship between EU rules and national-level implementation. Strengthening implementation requires both better national ownership of the rules and their application and greater congruence of national-level frameworks with EU-level rules. The former can only be achieved by rules that convincingly balance the needs of members with the avoidance of negative externalities across members. This argues for a risk-based approach-the first pillar of our proposal. The latter requires a stronger role for significantly upgraded national level frameworks-the second pillar of our proposal.